Estimation of Export Supply Function for Citrus Fruit in Pakistan (The Pakistan Development Review, 2005)
Nature has blessed Pakistan with an ideal climate for growing a wide range of delicious fruits. Thus a very wide range of tropical, sub-tropical and temperate fruits are grown in the country. Over the years, Pakistani experts have developed unique strains of exotic fruit varieties. Pakistan is producing a large variety of fruits on an area of 734.6 thousand hectares with a total production of 5712.4 thousand tons. Out of this 354.4 thousand tons fruit is exported from the country [Pakistan (2004)]. Horticulture is an important sub-sector of agriculture and plays a vital role not only in rejuvenation of rural economy but also in improving human nutrition which is often deficient in ingredients such as vitamins and minerals. Citrus and mango are the main fruit crops which contribute substantially to the national income.